2007
DOI: 10.21273/hortsci.42.7.1592
|View full text |Cite
|
Sign up to set email alerts
|

Node Type Development of Four Low-chill Peach Cultivars at Three Locations in Florida

Abstract: The effect of climate was observed on the relative frequency of vegetative and floral buds in four low-chill peach cultivars (‘Flordaprince’, ‘Flordaglo’, ‘UFGold’, and ‘TropicBeauty’). The trees were planted in north–central, central, and southwest Florida. The percentage of blind nodes, mixed nodes (nodes with vegetative and floral buds), and nodes with only vegetative buds were determined from three representative shoots per tree at each location. In general, higher percentages of blind nodes were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Generally, fruit set and cropping were higher for 'UFGold' than for 'TropicBeauty'. In a related study, Wert et al (2007a) found a greater incidence of blind nodes on 'TropicBeauty' than on 'UFGold'. Blind node development can reduce fruit set and have an effect on fruit size similar to flower or fruit thinning.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Generally, fruit set and cropping were higher for 'UFGold' than for 'TropicBeauty'. In a related study, Wert et al (2007a) found a greater incidence of blind nodes on 'TropicBeauty' than on 'UFGold'. Blind node development can reduce fruit set and have an effect on fruit size similar to flower or fruit thinning.…”
Section: Resultsmentioning
confidence: 87%
“…Generally blush values observed in southwest Florida agreed with previously reported information (Rouse and Sherman, 1989b;Lyrene, 1989, 1997;Sherman et al, 1982). Higher blush values at the central and southwest locations may also be attributable in part to higher incidence of blind nodes caused by higher temperatures during bud development at these locations than in north-central Florida (Wert et al, 2007a). This would allow for greater sunlight penetration into tree canopies at the warmer locations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in blind node frequency among cultivars and locations can have a large impact on the pruning and potential yield in peach (Wert et al, 2007). A wide range of blind node frequency (0% to 90%) has been reported for the University of Florida peach germplasm, demonstrating that there is genetic variability for blind node incidence, and breeding against this disorder should be feasible if its mode of inheritance can be determined (Richards et al, 1994).…”
mentioning
confidence: 99%
“…Higher rates of blind nodes are observed in warmer sites like central and southwest Florida than in north-central Florida (Wert et al, 2007). Trees grown in the highlands of the subtropics or coastal climates that have cool summers do not show blind nodes but when taken to warm humid climates such as Florida often exhibit this disorder (Richards et al, 1994).…”
mentioning
confidence: 99%